POLITIK ISLAH: RE-NEGOSIASI ISLAH, KONFLIK, DAN KEKUASAAN DALAM NAHDLATUL WATHAN DI LOMBOK TIMUR - Saipul Hamdi (Jurnal Kawistara, 2011)
This article aims to examine how islah or reconciliation was achieved by Nahdlatul Wathan’s elites. The conflict of NW in 1998 is a protracted one because the negotiation process of islah failed. Both groups did not find an appropriate point or an ideal format of islah proposal. Through long way process of negotiation, taking more than one decade, finally both group achieved an agreement of islah in May 2010. This article aims to explore the backgrounds and motivations of NW islah between both groups, as well as describe the efforts of undertaken by NW elite for conducting islah during times of conflict. This article also aims to understand what the format of islah has been achieved and how the NW maintain the continuity of islah commitment and agreement. This article is based on ethnographic research undertaken over a period of two years (2008-2010) in East Lombok, West Nusa Tenggara. The collecting and analyzing of data was done using the qualitative method; the collection of data was done using thetechniques of participant-observation, in-depth interview, and focus group discussion.Keywords: Islah, Politic, Conflict, Nahdlatul Wathan